STATUS OF MUSLIM WOMEN IN INDIA: A COMPREHENSIVE STUDY - Anjum, Shabana (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Today, Muslims – who make up 12 per cent of India’s total population – are India’s largest minority community. Islam came to the Indian subcontinent at various times and was assimilated in various ways. Nevertheless, Muslim rule lasted for nearly eight centuries, leaving a profound impact on India’s history, culture, politics and administration. In 712 AD, the Arab armies of Muhammad bin Qasim conquered a part of Balochistan, and reached the borders of Sindh. In Kashmir in the fourteenth century, Sufi orders from Persia and Central Asia combined local traditions with Islamic messages such as spirituality, equality and tolerance. The Rishi movement then emerged as a popular social discontent against the norms of Brahmanic society. In western India, the Dalit classes, attracted by Islam’s message of equality, embraced Sunni Islam, while other intermediate castes embraced Shiism. In South India, the influence of Muslim traders and their intermarriages led to the spread of Islam after the seventh century. After the Delhi Sultanate in 1192 AD, a quarter of India’s population became Muslim.